Hubungan Kompetensi Kepribadian Guru Pak Dengan Tingkah Laku Siswa Kelas VIII SMP Negeri 1 Laguboti Tahun Pelajaran 2024/2025 - Risma Darma Ulima Banurea; Wilson Simanjuntak; Baginda Sitompul; Oktober Tua Aritonang; Lasmaria Lumbantobing (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2024)
The purpose of this study is to find out the positive and significant relationship between the personality competence of PAK teachers and the behavior of grade VIII students of SMP Negeri 1 Laguboti for the 2024/2025 academic year. The hypothesis in this study is that there is a positive and significant relationship between the personality competence of PAK teachers and the behavior of grade VIII students of SMP Negeri 1 Laguboti for the 2024/2025 academic year. The method used in this study is an inferential descriptive quantitative method. The population is all Christian students in grade VIII of SMP Negeri 1 Laguboti for the 2024/2025 academic year totaling 219 people and a sample of 55 people is determined, namely 25% of the population using a simple random sampling technique. Data was collected with a positive closed questionnaire of 76 items, namely 46 items for variable X and 30 items for variable Y. The results of data analysis showed that there was a positive and significant relationship between the personality competence of PAK teachers and the behavior of grade VIII students of SMP Negeri 1 Laguboti for the 2024/2025 academic year as evidenced by the following data analysis: 1) a positive relationship test obtained a value of rxy = 0,544 > r table (=0,05,n=55) = 0,226 is in the medium category, thus it is known that there is a positive relationship between variable X and variable Y. 2) A significant relationship test obtained a thitung= 4,720 > ttabel(=0,05,dk=n-2=52)= 2,000 thus there is a significant relationship between variable X and variable Y. So Ha who said that there is a positive and significant relationship between the personality competence of PAK teachers and the behavior of grade VIII students of SMP Negeri 1 Laguboti Year The 2024/2025 lessons are accepted.